Reformulasi Strategi Pembelajaran Bahasa Arab di Era Disrupsi Digital: Perspektif Kontemporer Pendidikan di Indonesia - Aldereza Lidiya Mazyuna; Mad'ali Mad'ali (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This article aims to examine the challenges and solutions in Arabic language learning in Indonesia in the face of the digital disruption era. Using a qualitative approach through literature review, the study analyzes relevant sources related to Arabic language education, educational technology development, and 21st-century skills requirements. The findings indicate that learning is still dominated by conventional methods, lacks technological integration, and shows weak mastery of the four language skills (maharah lughawiyah). As a solution, this article proposes innovative, technology-based learning strategies, including the use of interactive digital media, communicative approaches, and creative instructional design tailored to the needs of the digital generation. It is expected that these ideas can serve as a reference for developing more effective and relevant Arabic language curricula and teaching practices.